The contribution of tourism to the development of Central and Eastern European countries in the new post-endemic and geostrategic context - Rodica Pripoaie; Anca Gabriela Turtureanu; George-Cristian Schin; Andreea-Elena Matic; Carmen-Mihaela Cretu; Cristina-Gabriela Păatrascu; Carmen-Gabriela Sîrbu; Emanuel \~nStefan Marinescu (Administrative Sciences, 2023)
This study explores an important issue in tourism, namely, the competitiveness of tourism. In the present paper, we aim at analyzing the relationship between tourism and national prosperity. The term competitiveness is a research topic intensively addressed in various fields, and it can answer current research questions related to a constantly changing tourism industry. Thus, the possibility of knowing how competitive this particularly important sector is for the five emerging countries considered in the study, namely, the Czech Republic, Hungary, Poland, Romania, and Slovakia, allows public authorities and entrepreneurs to estimate the revenues that can generate the field of hospitality. Also, based on these results, a series of national strategies specific to the tourism industry can be founded to lead to the increase of its competitiveness. We used cross-country multiple regression analysis to determine variables that are particularly important for the competitiveness of the hospitality industry, a fact for which the study has a theoretical and practical applicability. The study offers the possibility to anticipate the values of this index (TTCI), thus enabling government and industry bodies to take the necessary steps to increase specific competitiveness in the international market.
Keywords: 350; competitiveness; development; Travel & Tourism Competitiveness Index; cross-country multiple regression analysis